Modelo para a análise econômica e financeira em projetos para geração distribuída de energia com fontes alternativas - Wottrich, Breno (2010)
The implementation of distributed generation (DG) offers many benefits to the society, the electrical sector where they operate, and the consumers connected to the network especially due to their electricity self-production. For this case, proponents normally fight against costs estimation problems in projects of DG. In this way, low-cost and quality pre-feasibility studies are crucial when choosing the best financial and economical option. This Master thesis works on a specific methodology, with the software HOMER®, to the economic and financial (as well technical) prefeasibility study of projects with several small DG sources connected to middle voltages. A case study is also implemented with input data collected in the region of the Federal University of Santa Maria (UFSM). Therefore, it is developed a structure enclosing the general and interdisciplinary context of the projects. It helps the decision making process concerning the best-cost criterion option to advance to a more detailed viability study. As a result, this analysis of small DG systems proved to be very insightful, aligning its general objectives with the preciseness of pointing out promising technologies (wind turbines and microturbines fuelled by biogas) for further detailed studies.